Single Atom Ru Monolithic Electrode for Efficient Chlorine Evolution and Nitrate Reduction - Yao, Yancai; Zhao, Long; Dai, Jie; Wang, Jiaxian; Fang, Chuyang; Zhan, Guangming; Zheng, Qian; Hou, Wei; Zhang, Lizhi (Angewandte Chemie International Edition, 2022)
Fabricating single‐atom electrodes via atomic dispersion of active metal atoms into monolithic metal supports is of great significance to advancing the lab‐to‐fab translation of the electrochemical technologies. Here, we report an inherent oxide anchoring strategy to fasten ligand‐free isolated Ru atoms on the amorphous layer of monolithic Ti support by regulating the electronic metal‐support interactions. The prepared Ru single atom electrode exhibited exceptional electrochemical chlorine evolution activity, three orders of magnitude higher mass activity than that of commercial dimensionally stable anode, and also selectively reduced nitrate to ammonia with an unprecedented ammonia yield rate of 22.2 mol g−1 h−1 at −0.3 V. Furthermore, the Ru single atom monolithic electrode can be scaled up from 2×2 cm to 25×15 cm at least, thus demonstrating great potential for industrial electrocatalytic applications. We report an inherent oxide anchoring strategy to synthesize monolithic single atom electrodes. The prepared Ru single atom electrode exhibited exceptional electrochemical chlorine evolution and nitrate reduction performances. The scalability and bifunctionality of Ru single atom electrode highlight its great potential of electrochemical applications.